2022
DOI: 10.1016/j.jvoice.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Dysphonia and Vocal Tract Discomfort While Working From Home During COVID-19

Abstract: During COVID-19, government measures to prevent disease spread included advice to work from home. In addition to occupational risk factors, the increased use of telecommunication and changed work environment may contribute to voice and vocal tract discomfort (VTD). This study established the prevalence, incidence, characteristics and impact of self-perceived dysphonia and VTD in those working from home during COVID-19. Methods. A cross-sectional, observational study using an online survey recruited 1575 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 32 publications
4
27
0
8
Order By: Relevance
“…The prevalence of perceived voice alterations prior to the pandemic (32%) was similar to that reported in a recent study of people who were working remotely during the pandemic 10 and reinforces the high risk of dysphonia in this professional group. Although most of the participants did not report previous vocal changes, the proportion that did was higher than that reported in Behlau et al 3 and Devadas et al 21 ; those authors reported values close to 50% in the literature but emphasized that comparisons are difficult to make due to difference in methodologies.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The prevalence of perceived voice alterations prior to the pandemic (32%) was similar to that reported in a recent study of people who were working remotely during the pandemic 10 and reinforces the high risk of dysphonia in this professional group. Although most of the participants did not report previous vocal changes, the proportion that did was higher than that reported in Behlau et al 3 and Devadas et al 21 ; those authors reported values close to 50% in the literature but emphasized that comparisons are difficult to make due to difference in methodologies.…”
Section: Discussionsupporting
confidence: 85%
“…Psychological stress is one of the main factors associated with vocal symptoms in teachers. 4 , 9 , 10 Additionally, some of the teachers in this study reported experiencing vocal exhaustion. Because their voice is fundamental to their profession, teachers’ stress may increase as they notice vocal symptoms and/or difficulties with communication.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In this new reality, hybrid contexts, in which some activities can be implemented in person and others at a distance, have become common. This context has not been different in the area of speech therapy, and recent research on voice has been dedicated to understanding the following: professional vocal use during this pandemic period, especially in singers (6); the impact of wearing facemasks (7); the risks of vocal changes in different professionals who are working remotely (8,9); and the challenge of virtual voice therapy (10,11). The teacher's voice has been one of the themes most researched by specialists for decades, especially regarding symptoms and risk factors.…”
Section: ' Introductionmentioning
confidence: 99%